KINERJA PERANGKAT DESA DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR DESA PARIJATAH KULON KECAMATAN SRONO KABUPATEN BANYUWANGI - Oktaviyani, Bella; Wilujeng, Sri; Imaniar, Dimas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2024)
The Performance Of Village Office In The Implementation Of Public Service In Village Office Of Parijatah Kulon Village, Srono District, Banyuwangi Regency. Along with the times, society demands high value public sercices from the government, even though these demands are repeteadly not in line with expectations, because public services have so far been less professional. To improve of service, a performance at the village office cannot work without a village apparture. This improvement in the quality of performance village apparature to save time in fulfilling the functions of village officials and aims to improve the work discipline of an employee works, so that the result obtined are in accordace with thw services ecpected by the community. The research method used in thid study is a qualitative approach, where the research is descriptive in nature which describe the phenomena in the field being studied. For data collection techniques is Observation, Interview, Documentation, and Triangulation. The use of this qualitative method aims to obtain in depth information about the performance of the Parijatah Kulon Village Apparature in the implementation of public services. The performance of this village apparature as invetigated using T.R Mitchell’s theory which has five aspects is quality, promptness, initiative, capability, and communication.